EVAPOTRANSPIRATION AND CROP COEFFICIENT OF LETTUCE IN THE SOUTHWEST REGION OF THE STATE OF PARANÁ, BRAZIL - NUNES, Anderson Luis; BISPO, Noryam Bervian; HERNANDEZ, Ricardo Hernandez; NAVARINI, Lucas (Scientia Agraria, 2009)
The evapotranspiration (ETc) and crop coefficient (Kc) of lettuce were determined in two growing seasons (winter and autumn) using percolation lysimeters. During the winter and autumn growing seasons, total ETc average observed was, respectively, 162 mm and 181 mm. The Kc reached in both growing seasons its maximum in the moment of harvest. In winter and autumn the maximum value of Kc was nearly 1.40. This value is bigger than Kc suggested by FAO (1.00). By linear regression was ascertained what Kc values seemed to be strongly related to plant development.